Developing a Low-Sugar Dessert Business Idea with a Design Thinking Approach - Aripradono, Heru Wijayanto; Peiwen , Sally Tan (Newinera Publisher, 2024)
This research raises the issue of high sugar consumption which has a negative impact on public health. Data shows that sugar consumption in Indonesia is very high, making it one of the countries with the largest sugar consumption in the world. To overcome this problem, establishing a low-sugar dessert business is a very relevant solution. In this research, researchers used a qualitative descriptive method by adopting the Design Thinking approach as the main approach. Design Thinking is used to understand consumer needs and preferences and develop dessert products that are low in sugar but still delicious and satisfying. This method involves five stages, namely, empathy, defining the problem, ideation, prototyping, and testing. The research results show that the Design Thinking approach is successful in creating low-sugar dessert products that are well received by the market. The products resulting from this process not only meet health criteria but also satisfy consumer tastes, making them an attractive alternative to healthier desserts. This research also provides valuable insight into the market potential for low-sugar desserts and supports efforts to increase awareness of healthy eating among the public.